Poland's New Golden Age : Shifting from Europe's Periphery to its Center - Piatkowski, Marcin (World Bank, Washington, DC, 2014)
The objective of the paper is (i) to help fill the gap in knowledge on the long-term economic history of Poland; (ii) to provide a new perspective to the debate on the economic future of Poland, with a special focus on its historically unprecedented post-transition growth experience; and (iii) to analyze critically long-term growth projections for Poland. The paper argues that (i) Poland has just had probably the best 20 years in its economic history, growing the fastest among all European economies and one of the fastest worldwide; (ii) by 2013, it Poland achieved levels of income, quality of life, and well-being likely never experienced before, including relative to Western Europe, a natural benchmark; and (iii) Poland is well placed to continue converging with the Western European levels of income, permanently moving from the economic periphery of Europe, where it languished for centuries, to the European economic center. The twenty-first century thus promises to become Poland's new Golden Age. The paper calls for further research on the lessons from Poland's successful growth model for other countries in the region and beyond as well as on the long-term implications of the rise of Poland for the future of Europe.